The Effects of Organizational Justice and job Motivation on Organizational Citizenship Behavior and its Impact on Taxpayers - Ghazi, Mobina; Jalali, Seyed Mahdi (Revista Administração em Diálogo - RAD, 2017)
This study investigate the impact of organizational justice and job motivation on organizational citizenship behavior and its impact on satisfaction and loyalty of taxpayers. The statistical population of this study was formed by 7191 tax affairs of Tehran employees. Exploratory and confirmatory factor analysis method was used to evaluate the construct validity and standardization of research. Cronbach's alpha coefficient of questionnaire that calculated 0/97 was used to achieve Reliability of study. Therefore in this study, based on previous research and literature, the conceptual model and hypotheses were developed and tested on a sample of 401 person. Results of data analysis using structural equation modeling showed that all job related characteristics (except for feedback) on all aspects of job motivation, job motivation and organizational justice (except interactional justice) on OCB and Finally OCB is significant because of the satisfaction and loyalty of taxpayers and were confirmed.